Prevalence of congenital anomalies in a tertiary care centre in North Kerala, India - S., Jayasree; D'Couth, Smitha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Congenital anomalies have emerged as an important cause for neonatal morbidity and mortality. The prevalence as well as pattern of anomaly varies from place to place. Literature search reveals that India has the highest number of children with birth defects. Methods: This is a cohort study conducted in the Department of Obstetrics and Gynecology during the period 2009-2015. All mothers admitted with congenital structural defects to the fetus diagnosed by imaging and those who delivered anomalous babies were included in this study. The anomalies were classified based on ICD-10 system. Results: There were a total of 911 anomalous babies born during the study period of which 554 were males and 338 were females.19 babies had ambiguous genitalia. Anomalies were more common in multigravidae and in mothers of age group 20-29 years. Maximum number of babies were born between 37-40weeks. Maternal diabetes was associated with increased incidence of anomalies. Most common system involved was urinary system followed by musculoskeletal system. Conclusions: The prevalence of structural anomalies in the present study is 0.84%. Patients with risk factors for anomalies should undergo pre-pregnancy counselling. Routine antenatal anomaly screening with ultrasound before viability should be done for all patients so that early termination of lethal anomalies can be done.